Examining the Influence of Zinc Oxide Nanoparticles and Bulk Zinc Oxide on Rat Brain Functions: a Comprehensive Neurobehavioral, Antioxidant, Gene Expression, and Histopathological Investigation - Amira A. Goma; Alyaa R. Salama; Hossam G. Tohamy; Rashed R. Rashed; Mustafa Shukry; Sara E. El-Kazaz (Biological Trace Element Research, 2024)
The study aimed to assess the impact of zinc oxide nanoparticles (ZnONPs) on rats’ neurobehavior compared to bulk zinc oxide (BZnO). Thirty male Sprague-Dawley rats were randomly assigned to five groups. The control group received Tween 80 (10%), while the ZnONP groups were given ZnONPs at 5 and 10 mg/kg body weight dosages, and the bulk zinc oxide (BZnO) groups received BZnO at the same dosages. Behavioral observations, neurobehavioral examinations, and assessments of brain tissue oxidative markers, neurotransmitter levels, and histopathological changes were performed. The results indicated that ZnONP at a dosage of 5 mg/kg improved general behavior, locomotor activity, memory, and recognition and reduced fearfulness in rats. Conversely, the higher dosage of 10 mg/kg and the bulk form had adverse effects on general behavior, locomotor activity, and learning ability, with the bulk form demonstrating the most severe impact—znONP-5 treatment increased antioxidant enzyme levels and decreased inflammatory markers. BZnO-5 exhibited lower oxidative stress markers, although still higher than BZnO-10. Furthermore, ZnONP-5 and BZnO-5 increased neurotransmitter levels compared to higher dosages. ZnONP-5 upregulated the expression of brain-derived neurotrophic factor (BDNF) mRNA, while BZnO-5 showed increased BDNF mRNA expression and decreased expression of genes related to apoptosis and inflammation. In summary, ZnONPs at 5 mg/kg demonstrated positive effects on rat brain function and behavior, while higher dosages and the bulk form had detrimental effects. In conclusion, the studies emphasized the importance of further assessing various doses and forms of zinc oxide on brain health, highlighting the significance of dosage considerations when using nanomaterials.